ASSESSING THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER RELATIONSHIP MANAGEMENT (CRM) EFFECTIVENESS - Tabassum, Rumana; S. Chitradevi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the influence of service quality on Customer Relationship Management (CRM) effectiveness, comparing public and private banks. Service quality is assessed through six key dimensions: Efficiency and Promptness, Customer Interaction and Communication, Transparency and Clarity, Convenience and Accessibility, Issue Resolution, and Reliability and Consistency. Using regression analysis, the study identifies the most significant predictors of CRM effectiveness in both banking sectors. The findings indicate that while both public and private banks exhibit strong service quality impacts on CRM, private banks demonstrate a more robust correlation, with Transparency and Clarity emerging as the most influential factor. These insights highlight the need for targeted service quality improvements to enhance CRM effectiveness, particularly in public banks.